ANALISIS CONJOINT PAIRWISE-COMPARISON UNTUK MENGETAHUI TINGKAT KEPENTINGAN ATRIBUT JASA BIRO PERJALANAN WISATA (Studi Kasus Beberapa SMA Negeri di Kabupaten Klaten) - Galih Maraseta W H Prasaja; Yuciana Wilandari; Sudarno Sudarno (Jurnal Gaussian, 2014)
Competition in the business world travel agency today's increasingly stringent. Travel agency is a business that organizes tourist activities and other services related to the operation of the tour both domestically and abroad in a foreign country. To help business people of the travel agency in knowing and understanding consumer preferences on a combination of attributes of a travel agency conjoint analysis can be used. In this study conjoint analysis is used by using presentation method of pairwise-comparison. There are four attributes used in this analysis, they are bus facilities, agency facilities, hotel, and dining facilities. From the results of the analysis that obtained by the respondents, the most important attribute in selecting a travel agency is the dining attribute with a relative importance value of 38,02%. The next most important attribute according to the respondents is the attribute of the bus facility with a relative importance value of 28,46%, attributes agency facilities with a relative importance value of 19,58%, attributes the hotel facilities with a relative importance value of 13,94%. The combination of desired respondents in choosing or use the services of a travel agency is a travel agency with wifi bus facilities, hotel facilities with the large bed, an agency facility of video documentation and a buffet meal.